Istinbat Law of Ru'yah al-Hilāl of The PBNU Falakiyah Institute (Study on The Cancellation of Istikmal In The Month Of Jumadil Awal 1438 H/2017 M) - Ashidiqi, Iqnaul Umam; Abdul Haq, M. Adib (JOURNAL OF ISLAMIC AND LAW STUDIES, 2025)
Determination of the beginning of the month of Jumadil Akhir 1438 H, the position of the hilal based on hisab at an altitude of 7˚08' - 8˚51'in Indonesia no one managed to see the hilal. Therefore, the beginning of Jumadil Akhir 1438 H was decided on March 1, 2017 on the basis of ikmal / istikmal. On Tuesday, March 28, 2017, there was a rukyat report in Pelabuhan Ratu of the hilal at 3˚27' and in Condrodipo Gresik, at 3˚17' there was a person who saw the hilal and his report was accepted, resulting in the istikmal of the month of Jumadil Awal being canceled. The purpose of this study is to reveal the legal istinbāṭ of the cancellation of ikmal / istikmal in the month of Jumadil Awal 1438 AH / 2017 AD. This research uses a library research method which is included in the qualitative type with an evaluative descriptive approach, which means that the author seeks to reveal and understand the implementation of ru'yah al-hilal in the perspective of the PBNU LF in the case of a Study on the Cancellation of Istikmal in the Month of Jumadil Awal 1438 H / 2017 AD). The conclusion of the legal istinbāṭ used and referred to by the PBNU LF is through the results of the NU XXXIV Congress in Lampung. Contradictions between material and formal provisions in the Hijri calendar can also occur. In order to unravel the problem of contradictions in the lunar calendar, the LF PBNU uses the al-Tarjih method as a solution.